2019
DOI: 10.1080/09687637.2018.1557595
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana sources in a medical marijuana environment: dynamics in access and use among a cohort of young adults in Los Angeles, California

Abstract: While a range of sources exist for marijuana users to acquire marijuana for medical or personal use, prior research on marijuana sources primarily focused on single sources. In this analysis, we longitudinally examined characteristics of multiple sources selected by marijuana users, motivations to use sources, and how a blend of marijuana sources accommodated users' needs. Young adult marijuana users (n=60) in Los Angeles, CA, where marijuana has been legal for medical use since 1996, completed two annual qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Price is a well-known determinant of black market use [ 28 , 29 ], but lower price also facilitates greater use on a population level, which could be detrimental to public health. Although participants indicated that their preference for black market cannabis products is primarily driven by price, they also noted easy access, confidence in identifying high quality “street products,” and trust of their “street sellers” [ 30 ] as additional reasons to use the informal black market. Our findings suggest that Nevada’s current legal recreational cannabis infrastructure does not encourage price-sensitive young adult cannabis users of legal purchase age to abandon the high-risk black market for the regulated, legal cannabis market.…”
Section: Discussionmentioning
confidence: 99%
“…Price is a well-known determinant of black market use [ 28 , 29 ], but lower price also facilitates greater use on a population level, which could be detrimental to public health. Although participants indicated that their preference for black market cannabis products is primarily driven by price, they also noted easy access, confidence in identifying high quality “street products,” and trust of their “street sellers” [ 30 ] as additional reasons to use the informal black market. Our findings suggest that Nevada’s current legal recreational cannabis infrastructure does not encourage price-sensitive young adult cannabis users of legal purchase age to abandon the high-risk black market for the regulated, legal cannabis market.…”
Section: Discussionmentioning
confidence: 99%
“…This partial failure in the transition to legal cannabis sources for personal supply may reflect a number of factors including: restricted availability and access (e.g. limited locations, opening hours) of legal sources (Fischer, 2017; Kilmer & Pacula, 2017; Lancione et al, 2020; Pardal et al, 2019; Reed et al, 2020) and age restrictions (21 in all US, mostly 19 in Canadian jurisdictions), higher prices in the legal sector and restrictions on the products legally available. Uruguay in particular has tight restrictions both on the potency of legally retailed cannabis and on the modes of access (Queirolo, 2020); for example users must register to use only one of the three modes of access (home grow; joining a growers club or purchasing from a pharmacy).…”
Section: Introductionmentioning
confidence: 99%
“…Price is a well-known determinant of black market use [28][29] , but lower price also facilitates greater use on a population level, which could be detrimental to public health. Although participants indicated that their preference for black market cannabis products is primarily driven by price, they also noted easy access, con dence in identifying high quality "street products", and trust of their "street sellers" 30 as additional reasons to use the informal black market. Our ndings suggest that Nevada's current legal recreational cannabis infrastructure does not encourage price-sensitive young adult cannabis users of legal purchase age to abandon the high-risk black market for the regulated, legal cannabis market.…”
Section: Discussionmentioning
confidence: 99%